2013
DOI: 10.1111/bph.12404
|View full text |Cite
|
Sign up to set email alerts
|

Fluocinolone acetonide partially restores the mineralization of LPS‐stimulated dental pulp cells through inhibition of NF‐κB pathway and activation of AP‐1 pathway

Abstract: BACKGROUND AND PURPOSEFluocinolone acetonide (FA) is commonly used as a steroidal anti-inflammatory drug. We recently found that in dental pulp cells (DPCs) FA has osteo-/odonto-inductive as well as anti-inflammatory effects. However, the mechanism by which FA induces these effects in DPCs is poorly understood. EXPERIMENTAL APPROACHThe effect of FA on the mineralization of DPCs during inflammatory conditions and the underlying mechanism were investigated by real-time PCR, Western blot, EMSA, histochemical stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 28 publications
(26 reference statements)
2
27
0
Order By: Relevance
“…A previous study with dental pulp cells reported the presence of other transcription factors of AP‐1 (Fra‐1 and c‐Jun) in untreated cells (Liu et al . ). Further studies should be performed to understand the location and performance of Jun‐D during odontoblastic differentiation.…”
Section: Discussionmentioning
confidence: 97%
“…A previous study with dental pulp cells reported the presence of other transcription factors of AP‐1 (Fra‐1 and c‐Jun) in untreated cells (Liu et al . ). Further studies should be performed to understand the location and performance of Jun‐D during odontoblastic differentiation.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding the clinical application of GCs, FA is currently mainly used for dermal, dental, and ophthalmological prescriptions, whereas its close counterparts, TA and DEX, have been already used for intraarticular injections in the management of joint diseases . Although application of GCs in rheumatoid arthritis and other joint diseases is widely adopted, long‐term application of GCs have been recognized to be harmful to cartilage .…”
Section: Discussionmentioning
confidence: 99%
“…The results of western blotting showed that NCPB treatment can significantly inhibit the degradation of IκB and decrease the expression of p65, as well as decreasing the nuclear translocation of p65. The expressions of c-Jun are correlated to the activity of AP-1 [22], our work demonstrated that NCPB can decrease the expressions of c-Jun of the macrophages, and suppress its nuclear translocation. In addition, our results also indicated that NCPB can also decrease the DNA binding activities of NF-κB and AP-1.…”
Section: Discussionmentioning
confidence: 54%